Composite fish culture in a rain-fed seasonal tank - Piska, Ravishankar (Indian Journal of Fisheries, 2011)
The study deals with the composite fish culture in a rain-fed seasonal tank(area : 1.5 ha; depth : 0.2-1.25 m). The carps, Labeo rohita, Catla catla, Cirrhinamrigala and Cyprinus carpio were the candidates cultured. The fingerlings of thecarps were reared for 6 months after accumulation of rain water in the tank.Growth rate of C. carpio was found to be more, while the survival rate was morein the case of L. rohita. When considered for all the species the survival ratewas low (28.26 to 41.35%) and a total production of 977.75 kg/ha/6 months of fishwas obtained. C. carpio yielded more (544.08 kg/ha/6 months) when comparedto the other fishes.